Life without ice: Perceptions of environmental impacts on marine resources and subsistence users of St. Lawrence Island. (15th October 2021) - Larsen Tempel, Jenell T.; Wise, Sarah; Osborne, Tonia Q.; Sparks, Kim; Atkinson, Shannon
Abstract: The Bering Strait region is undergoing rapid environmental change linked to reductions in the extent and seasonal availability of sea ice. The goal of the present study was to assess the impacts that environmental change and loss of sea ice has had on marine subsistence resources and resource users in the communities of St. Lawrence Island (SLI), Alaska. The broader research design was multidisciplinary in order to document any shifts in the abundance and health of key marine subsistence species, while recording people's perceptions of changing environmental conditions in their lifetime. The present study focuses on the perceived social and material effects of climate change on SLI residents. To capture human perceptions and experiences, open ended interviews were conducted during three weeks in April and May 2019, during which time 25 SLI residents were interviewed. Four main themes were assessed: 1) key marine resources for SLI communities, 2) perceptions about changes in key resources, 3) community responses to change, and 4) the future of the subsistence way of life in these communities. Interviews were transcribed, coded for themes, and analyzed using MAXQDA software. Results indicate the four most discussed marine resources were Pacific walruses ( Odobenus rosmarus divergens ), seals, crabs, and fish. The largest changes observed in these resources included: decreased walrus harvests and limited access with increased hunting effort; an increase in the abundance of Hanasaki crab ( Paralithodes brevipes ) and limited crab harvests due to lack of shorefast ice; and increasing abundances of walleye pollock ( Gadus chalcogrammus ) and Pacific cod ( Gadus macrocephalus ). SLI residents utilize a broad range of edible marine flora and fauna, and at times, eat less desirable prey items due to scarcity of preferred species. Lastly, most informants that discussed the future of a subsistence way of life, were concerned future generations will be harvesting and eating less subsistence resources. Due to environmental changes, and most specifically loss of sea ice, SLI communities may have to diversify the species that they harvest to continue maritime subsistence practices, or may turn to consuming more terrestrial and domestic sources of protein if available. To better understand resource availability and to manage for a changing ecosystem, resource managers and policy makers may: 1) anticipate a need for conducting stock assessments for king and Hanasaki crabs at regular intervals, 2) anticipate a need for conflict resolutions, mitigation frameworks, or agreements if commercial fishing vessels encroach on space and resources traditionally used by SLI subsistence users, and 3) take an active approach in obtaining authorizations for the harvest of currently protected marine mammals, which may be needed to ensure food security and consumption of historically traditional foods from the local environment. Graphical abstract: Image 1 Highlights: Informants are concerned about ice-related calf/pup mortalities of walruses and seals. Informants are traveling farther to access walruses than in the recent past. Hunters are practicing a more opportunistic marine mammal hunting style. King and Hanasaki crab and are key resources that lack stock assessments. Changing commercial fish stocks may lead to increases in local fishing pressure.